Can someone help me understand my mistake???
m1v1 + m2v2 = (m1+2)vf = pf
20 * 5 + 5 * 0 = pf
100 kg * m/s= pf
25 kg * 5 m/s = 125 kg m/s
(m1 + m2) * (v1 + v2)
I might be over thinking this question, I don’t understand why pf=vi * (m1+m2) with vi = vf
I was using the equation for inelastic collisions, and we should be loosing kinetic energy which is verified by
4= vf < vi so Ecf < Eci
Could someone help me understand? Thank you!
Its not technically an inelastic “collision” because she is already on the sled - its a weird question. It seems like they just want the combined mass x velocity.
The part they want you to mess up is the conversion.